2022
DOI: 10.22271/oral.2022.v8.i1c.1421
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sealing ability of four different root canal sealers using stereomicroscope: An in vitro study

Abstract: Introduction:The most commonly used core material for root canal filling is gutta-percha and as the gutta-percha by itself cannot obturate the complete root canal system, owing to its poor sealing properties hence, a sealer is used in combination with root filling material. Sealer is more important than the core obturating material. Sealer plays a secondary role by merely reinforcing (binding or luting) the guttapercha to the canal walls, however, it is now confirmed that the sealer has a prime role in sealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…They found that Eposeal exhibited the least dye penetration, followed by Bioroot RC, and Nanoseal S showed the highest dye penetration. Thakur et al [ 62 ] compared the apical sealing ability of four endodontic sealers: conventional zinc oxide eugenol sealer, Apexit, AH-Plus, and Roekoseal Automix (RSA). RSA, a polydimethylsiloxane-based sealer, demonstrated significantly better apical sealing compared to the other sealers.…”
Section: Discussionmentioning
confidence: 99%
“…They found that Eposeal exhibited the least dye penetration, followed by Bioroot RC, and Nanoseal S showed the highest dye penetration. Thakur et al [ 62 ] compared the apical sealing ability of four endodontic sealers: conventional zinc oxide eugenol sealer, Apexit, AH-Plus, and Roekoseal Automix (RSA). RSA, a polydimethylsiloxane-based sealer, demonstrated significantly better apical sealing compared to the other sealers.…”
Section: Discussionmentioning
confidence: 99%